THE TECHNOLOGY OF CREATING A PANEL USING THE KINUSAYGA METHOD (International journal of artificial intelligence, 2025)
This article explores the process of creating decorative panels using the Kinusayga method a unique Japanese art form that involves arranging small pieces of fabric into a base without the use of needles or thread. The paper discusses the historical origins of Kinusayga, its application in modern educational practice, and its artistic and pedagogical significance. The method enhances students’ aesthetic perception, creativity, precision, and patience. It is shown that Kinusayga not only develops artistic taste and fine motor skills but also promotes ecological awareness by reusing fabric remnants. The technique can be effectively used in technology and art classes to cultivate students’ imagination, sense of color harmony, and respect for cultural traditions.